Sexual maturation and fecundity of barfin plaice Liopsetta pinnifasciata - Valeria M. Latyshova; Maksim I. Boyko (Известия ТИНРО)
There is determined for barfin plaice Liopsetta pinnifasciata that individual and age variability of its eggs diameter is poorly expressed, relative fecundity has no age variability, individual fertility increases with age (from 53,000 to 730,000 eggs) proportionally to the gonads growth, males mature faster and reach puberty in the main in the first year of their life (percentage of spawning males/females is 68/12 in the age of 1 year, 100/31 in the age of 2 years, 100/45 in the age of 3 years, and only in the age of 4 years all females spawn), but females have longer life span and the females only are presented in the age 6+ and older, for the most part they live up to 10 years, reaching the length of 39 cm, and the maximal their age is 12 years. So, the males prevail in the younger age groups and the females in the elder age groups; periods of puberty are 7-8 years for females and 4-5 years for males that is 67-89 % of the life span for both sexes. The age groups 3+...6+ make the highest contribution to population fecundity.